The Role of the Courts in Advancing Water Security in South Africa - Qumbu, Bronwen (Potchefstroom Electronic Law Journal, 2021)
This article explores the role which courts could play in promoting water security in South Africa. As the country is one of the driest on the continent, its water security issues remain at the forefront of the service delivery conundrum. Therefore, issues of water security often need to be litigated to arrive at a favourable and just outcome. This is where the focus of this article lies. Based on a critical analysis of the legal framework governing water security and relevant case law, the article argues that courts could promote water security by discharging certain duties. Firstly, the courts must uphold the applicable law by weighing the rights and interests that relate to water and must then make reasonable, just and equitable findings. Secondly, the courts must solve water-related disputes between parties by interpreting and applying the applicable laws and policies. It is submitted that by executing these two functions, the courts contribute to a deeper understanding of the water security discourse. Finally, it is argued that through the execution of their traditional judicial functions, courts contribute to the making of law that directly affects water security.